Quantifying the impact of Wellington Zoo's persuasive communication campaign on post‐visit behavior. Issue 2 (4th February 2015) - MacDonald, Edith
<x xml:space="preserve">Abstract</x> Zoos potential to facilitate visitor conservation behavior is commonly articulated. Few studies, however, have quantified whether zoos' conservation messages result in visitors implementing the behavior. To test if zoo conservation messages are adopted at home, I implemented a persuasive communication campaign which advocated keeping cats indoor at night, a behavior that is a potential solution to cats depredating native wildlife. Furthermore, I tested if a public commitment (signing a pledge card) strengthened the relationship between on‐site intention to engage in the behavior and actual implementation of the behavior at home. The conservation behavior was included in the twice‐daily animal presentations in the amphitheater. A sample of 691 visitors completed a survey as they exited the amphitheater that measured their recall of the conservation behavior and intention to engage in the behavior at home. The last 311 visitors to complete the survey were asked to sign a pledge card which was publicly displayed in the amphitheater. Six weeks after their zoo trip, visitors were contacted and asked if they had implemented the behavior. Recall of the conservation behavior was high (91% for control, 100% for pledge group) and the entire pledge group had implemented the behavior whereas just half (51%) of the control group did. Furthermore, signing the pledge card strengthened the relationship between onsite intention and at home behavior (r = 1.0 of for the pledge group and r = 0.21 for the control group). Overall, the zoo's conservation message was recalled and behavior implemented at home. Zoo Biol. 34:163–169, 2015. © 2015 Wiley Periodicals Inc.